The First-Generation Whole-Genome Radiation Hybrid Map in the Horse Identifies Conserved Segments in Human and Mouse Genomes - Chowdhary, Bhanu P.; Raudsepp, Terje; Kata, Srinivas R.; Goh, Glenda; Millon, Lee V.; Allan, Veronica; Piumi, François; Guérin, Gérard; Swinburne, June; Binns, Matthew; Lear, Teri L.; Mickelson, Jim; et al. (Genome Research, 2003)
A first-generation radiation hybrid (RH) map of the equine (Equus caballus) genome was assembled using 92 horse × hamster hybrid cell lines and 730 equine markers. The map is the first comprehensive framework map of the horse that (1) incorporates type I as well as type II markers, (2) integrates synteny, cytogenetic, and meiotic maps into a consensus map, and (3) provides the most detailed genome-wide information to date on the organization and comparative status of the equine genome. The 730 loci (258 type I and 472 type II) included in the final map are clustered in 101 RH groups distributed over all equine autosomes and the X chromosome. The overall marker retention frequency in the panel is ∼21%, and the possibility of adding any new marker to the map is ∼90%. On average, the mapped markers are distributed every 19 cR (4 Mb) of the equine genome—a significant improvement in resolution over previous maps. With 69 new FISH assignments, a total of 253 cytogenetically mapped loci physically anchor the RH map to various chromosomal segments. Synteny assignments of 39 gene loci complemented the RH mapping of 27 genes. The results added 12 new loci to the horse gene map. Lastly, comparison of the assembly of 447 equine genes (256 linearly ordered RH-mapped and additional 191 FISH-mapped) with the location of draft sequences of their human and mouse orthologs provides the most extensive horse–human and horse–mouse comparative map to date. We expect that the foundation established through this map will significantly facilitate rapid targeted expansion of the horse gene map and consequently, mapping and positional cloning of genes governing traits significant to the equine industry.[Supplemental material is available online at www.genome.org. The following individuals kindly provided reagents, samples, or unpublished information as indicated in the paper: R. Brandon, G. Lindgren, and I. Tammen.]